The Influence of the Code of Ethics and Professional Responsibility of the Police in Performing Public Services and Law Enforcement in the Cilegon City Police Station - Sulasno Sulasno; Lolitawati Lolitawati; Putri Pratama Ayu Ningsih (Pusat Publikasi Nusantara, 2024)
This study aims to contribute to the field of police ethics and law enforcement by providing a comprehensive analysis of the factors leading to ethical violations, the responsibilities of police officers in maintaining ethical standards, and the effectiveness of law enforcement practices in dealing with such violations. Data analysis is carried out in a qualitative descriptive manner by understanding and assembling primary and secondary data that have been collected systematically to provide an overview of the problem being studied. Based on this theory, the factors that affect the occurrence of ethical violations and the responsibility of the police profession in carrying out public services and how to enforce the law on violations of the Code of Professional Ethics of the Police Professional Code of Ethics at the Cilegon City Police.